2019
DOI: 10.1007/s10620-019-05568-9
|View full text |Cite
|
Sign up to set email alerts
|

Exocrine Pancreatic Insufficiency Following Acute Pancreatitis: Systematic Review and Meta-Analysis

Abstract: Background/Objectives The epidemiology of exocrine pancreatic insufficiency (EPI) after acute pancreatitis (AP) is uncertain. We sought to determine the prevalence, progression, etiology and pancreatic enzyme replacement therapy (PERT) requirements for EPI during follow-up of AP by systematic review and meta-analysis. Methods Scopus, Medline and Embase were searched for prospective observational studies or randomized clinical trials (RCTs) of PERT reporting EPI during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
65
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 63 publications
(176 reference statements)
4
65
0
3
Order By: Relevance
“…Pancreatic diseases are often accompanied with PEI and malnutrition. In AP, prevalence of PEI during admission was 62 and 21-35% during follow up (Vujasinovic et al, 2014;Tu et al, 2017;Huang et al, 2019). After pancreatectomy, PEI was reported to develop in 36-76% of the patients with mean time to onset of 14-40 months (Lee et al, 2013;Beger et al, 2018;Hallac et al, 2019;Kusakabe et al, 2019).…”
Section: Potential Dep Pathological Mechanisms Based On Pancreatic Exmentioning
confidence: 98%
“…Pancreatic diseases are often accompanied with PEI and malnutrition. In AP, prevalence of PEI during admission was 62 and 21-35% during follow up (Vujasinovic et al, 2014;Tu et al, 2017;Huang et al, 2019). After pancreatectomy, PEI was reported to develop in 36-76% of the patients with mean time to onset of 14-40 months (Lee et al, 2013;Beger et al, 2018;Hallac et al, 2019;Kusakabe et al, 2019).…”
Section: Potential Dep Pathological Mechanisms Based On Pancreatic Exmentioning
confidence: 98%
“…EPI is almost always produced by a pancreatic disease, with the most frequent cause being chronic pancreatitis in adults [ 10 , 11 ] and cystic fibrosis in children [ 4 ]. Other etiologies include acute pancreatitis [ 12 , 13 ], pancreatic tumors [ 14 ], diabetes mellitus [ 15 , 16 ], celiac disease, inflammatory bowel disease [ 17 , 18 ], gastrointestinal and pancreatic surgery [ 19 , 20 , 21 ], HIV and genetic and congenital factors. Some of these causes have are less frequent, and there is even debate around their true role in the etiology of EPI.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, methods used to detect and measure EPI are extremely varied among studies, making it difficult to draw conclusions on the true prevalence of EPI. In this current systematic review and meta-analysis, Huang et al [1] were able to determine the pooled prevalence of EPI during the index hospitalization for AP and during follow-up, in contrast to the only other large-scale meta-analysis that was focused on EPI after AP, reported by Holleman et al [2], that measured the prevalence of EPI following AP only during up to 36 months of follow-up. Huang et al found that the cumulative prevalence of EPI in all studies with AP was a rather shocking 62%, when including those with EPI at any point during the index hospitalization, much greater than the 27% prevalence reported in previous meta-analysis [2].…”
mentioning
confidence: 89%
“…While clinicians might recognize that EPI could develop after an episode of severe acute pancreatitis (AP) associated with significant pancreatic necrosis, it is becoming more apparent that EPI may occur even in those with less severe episodes of AP. The systematic review and meta-analysis published in this issue of Digestive Diseases and Sciences [1] provide an estimate of the prevalence and predictors of EPI after AP.…”
mentioning
confidence: 99%